2005
DOI: 10.1063/1.1856222
|View full text |Cite
|
Sign up to set email alerts
|

Silent Raman modes in zinc oxide and related nitrides

Abstract: Anomalous Raman modes have been reported in several recent papers dealing with doped-and undoped-ZnO layers grown by different methods. Most of these anomalous Raman modes have been attributed to local vibrational modes of impurities or defects. However, we will show that most of the observed modes correspond to wurtzite-ZnO silent modes allowed by the breakdown of the translational crystal symmetry induced by defects and impurities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
211
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 357 publications
(233 citation statements)
references
References 44 publications
19
211
2
1
Order By: Relevance
“…However, the Raman spectrum of the DZ phase would rather resemble that of the first-order one-phonon density of states of the zinc blende phase because disorder of cations and vacancies at cation sites will promote defect-induced or defect-assisted Raman scattering (DARS) due to the loss of the translational symmetry of the crystal. This Raman activity has been observed in many disordered, nanocrystalline, and pressure-treated compounds; [33][34][35][36] however, as already commented, no Raman scattering similar to a one-phonon density of states of the zinc blende phase has been ever reported to occur at high pressures neither above the pressure range 11-14 GPa in DCCdGa 2 Se 4 nor in other adamantine ternary OVCs at high pressures. 11,12,19,20 In fact, Ursaki et al concluded, from the analysis of their Raman results, 11 that the decrease of the intensity of the A 1 mode above 11 GPa was due to the onset of a second stage of disorder where all cations and vacancies mixed together, thus leading to the DZ phase in good agreement with the theoretically predicted stages of disorder proposed by Bernard and Zunger for OVCs at high temperatures but not for high pressures.…”
Section: -mentioning
confidence: 99%
“…However, the Raman spectrum of the DZ phase would rather resemble that of the first-order one-phonon density of states of the zinc blende phase because disorder of cations and vacancies at cation sites will promote defect-induced or defect-assisted Raman scattering (DARS) due to the loss of the translational symmetry of the crystal. This Raman activity has been observed in many disordered, nanocrystalline, and pressure-treated compounds; [33][34][35][36] however, as already commented, no Raman scattering similar to a one-phonon density of states of the zinc blende phase has been ever reported to occur at high pressures neither above the pressure range 11-14 GPa in DCCdGa 2 Se 4 nor in other adamantine ternary OVCs at high pressures. 11,12,19,20 In fact, Ursaki et al concluded, from the analysis of their Raman results, 11 that the decrease of the intensity of the A 1 mode above 11 GPa was due to the onset of a second stage of disorder where all cations and vacancies mixed together, thus leading to the DZ phase in good agreement with the theoretically predicted stages of disorder proposed by Bernard and Zunger for OVCs at high temperatures but not for high pressures.…”
Section: -mentioning
confidence: 99%
“…We attribute its observation to disorder-activated Raman scattering since it is known that many silent modes become Raman active as a consequence of structural disorder. 48 In fact, in a previous work on the Zn 1Àx Mn x Ga 2 Se 4 series, a broad band appearing around 180 cm À1 in the Raman spectra of all compounds of the series, either with SG I-42 m or I-4 was assigned to disorder activated vibrations having a similar pattern as the A 2 mode. 49 Consequently, with all these considerations, we have tentatively assigned this broad band to the silent A 2 1 mode [see open triangles in Fig.…”
Section: Hp Raman Measurements Of Ds-znga 2 Sementioning
confidence: 99%
“…However, as-grown samples generally do not exhibit this mode, since H is bound to Mg in Mg-N-H complexes, which are Raman-silent in this range. 16 An annealing step is necessary in order to break the complex, to allow H to diffuse towards the sample surface, and to finally reveal the free-Mg LVM. [17][18][19] As expected and as seen in Fig.…”
mentioning
confidence: 99%